Exploration—exploitation strategy is dependent on early experience. Issue 3 (18th March 2015) - Humphreys, Kathryn L.; Lee, Steve S.; Telzer, Eva H.; Gabard‐Durnam, Laurel J.; Goff, Bonnie; Flannery, Jessica; Tottenham, Nim
ABSTRACT: Traditional conceptualizations of early adversity characterize behavioral outcomes as maladaptive. However, conditional adaptation theory proposes that differing behavioral phenotypes following early experience are appropriate for the expected environment (e.g., behaviors likely to result in the best outcome based on environmental expectations). In the present study, youth with ( n = 46) and without ( n = 91) a history of previous institutionalization completed a laboratory‐based experimental paradigm in which exploration—exploitation strategy was examined, a phenotype relevant to environmental expectations. Previous institutionalization was associated with decreased exploration and increased exploitation. A strategy favoring exploration resulted in greater success in the generous task condition whereas a strategy favoring exploitation produced greater success in the restricted task condition. These results suggest that exploration—exploitation strategy may be influenced by early experience, and the resulting success of strategy choice is context dependent and in line with expectations of the future environment based on early experience. © 2015 Wiley Periodicals, Inc . Dev Psychobiol 57: 313–321, 2015.